Overcoming regulatory T‐cell suppression by a lyophilized preparation of Streptococcus pyogenes. Issue 4 (26th February 2013) - Hirayama, Michiko; Nishikawa, Hiroyoshi; Nagata, Yasuhiro; Tsuji, Takemasa; Kato, Takuma; Kageyama, Shinichi; Ueda, Shugo; Sugiyama, Daisuke; Hori, Sahoko; Sakaguchi, Shimon; Ritter, Gerd; Old, Lloyd J.; et al.
<x xml:space="preserve">Abstract</x> Cancer vaccines have yet to yield clinical benefit, despite the measurable induction of humoral and cellular immune responses. As immunosuppression by CD4+CD25+ regulatory T (Treg) cells has been linked to the failure of cancer immunotherapy, blocking suppression is therefore critical for successful clinical strategies. Here, we addressed whether a lyophilized preparation of Streptococcus pyogenes (OK‐432), which stimulates Toll‐like receptors, could overcome Treg‐cell suppression of CD4+ T‐cell responses in vitro and in vivo. OK‐432 significantly enhanced in vitro proliferation of CD4+ effector T cells by blocking Treg‐cell suppression and this blocking effect depended on IL‐12 derived from antigen‐presenting cells. Direct administration of OK‐432 into tumor‐associated exudate fluids resulted in a reduction of the frequency and suppressive function of CD4+CD25+Foxp3+ Treg cells. Furthermore, when OK‐432 was used as an adjuvant of vaccination with HER2 and NY‐ESO‐1 for esophageal cancer patients, NY‐ESO‐1–specific CD4+ T‐cell precursors were activated, and NY‐ESO‐1–specific CD4+ T cells were detected within the effector/memory T‐cell population. CD4+ T‐cell clones from these patients had high‐affinity TCRs and recognized naturally processed NY‐ESO‐1 protein presented by dendritic cells. OK‐432 therefore inhibits Treg‐cell function and contributes to the activation of high‐avidity tumor antigen‐specific naive T‐cell precursors.